Analysis of Displacement of Vibrating of Mass Spring Due to Opposition Force - Pokhrel, Puskar R.; Lamsal, Bhabani; Kafle, Jeevan; Kattel, Parameshwari (Tribhuvan University Journal, 2020)
Employing the model equation for mass spring system, which is of second order differential equation, we analyze the displacement with various opposition forces applied on the mass of the spring. We observe that if there is no external force on the mass of the spring, the opposition force causes the displacements of mass of spring. We also analyze the system by finding its analytic and numerical solution, and compare their results.